2011
DOI: 10.1007/s11701-011-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemiparesis after robotic laparoscopic radical cystectomy and ileal conduit formation in steep Trendelenburg position

Abstract: Robotic surgery is becoming popular for minimally invasive surgical procedures as robotic devices allow unprecedented control and precision. We report a case of robotic radical cystectomy with ileal conduit urinary diversion surgery having perioperative neurological complications related to prolonged surgery in the steep head-down position. There was a neurological deficit in the form of hemiparesis, which resolved with conservative management. We suggest that duration and positioning should be optimized for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 8 publications
2
42
0
1
Order By: Relevance
“…Fourth, the values for ICP, CBF, and CMRO 2 were not measured directly, which should be rectified in future research. Fifth, we limited the time spent with a pneumoperitoneum in the Trendelenburg position to 120 min, yet there have been reports of neurological complications due to brain edema when this procedure exceeds 8 h [29]. Actually, cerebrovascular autoregulation gradually changes with prolonged pneumoperitoneum in the Trendelenburg position; one study showed that it is decreased from 170 min [19].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the values for ICP, CBF, and CMRO 2 were not measured directly, which should be rectified in future research. Fifth, we limited the time spent with a pneumoperitoneum in the Trendelenburg position to 120 min, yet there have been reports of neurological complications due to brain edema when this procedure exceeds 8 h [29]. Actually, cerebrovascular autoregulation gradually changes with prolonged pneumoperitoneum in the Trendelenburg position; one study showed that it is decreased from 170 min [19].…”
Section: Discussionmentioning
confidence: 99%
“…Kalmar et al . () report no neurological or cognitive deficit after 160 min of surgery, but neurological deterioration subsequent to cerebral oedema is seen after long‐lasting surgery (7–10 h) (Pandey et al ., ). On the other hand, postoperative nausea and vomiting are more frequent with Trendelenburg's as opposed to reverse Trendelenburg's positioning (Patel et al ., ) acknowledging that different surgical procedures may have affected these findings.…”
Section: Discussionmentioning
confidence: 97%
“…Cerebral autoregulation has been observed to deteriorate when the Trendelenburg position lasts for more than 170 min and a case with brain edema and pathophysiologic changes in neuronal function was attributed to the operation Trendelenburg position; T20, T40, T60, T80, T100, T120, T140, T160, T180: 20, 40, 60, 80, 100, 120, 140, 160, and 180 min after Trendelenburg position; S: after return to supine position; HR: heart rate; SAP: systolic arterial pressure; DAP: diastolic arterial pressure; MAP: mean arterial pressure. exceeding 8 h in duration, with excessive Trendelenburg position and pneumoperitoneum (5). There are also publications reporting that increasing ICP, CBP, and CBV and decreasing carotid artery blood flow may negatively affect cerebral tissue oxygenation in patients with intracranial lesions during laparoscopy (6,7).…”
Section: Discussionmentioning
confidence: 99%